Analysis of Consumer Behavior in Choosing the ZPay Application as a Digital Transaction Service (Case Study at PT. ZPay Komunika Indonesia Gunungsitoli) - Zendrato, Hasrat Damai Aprilliaman; Mendrofa, Yupiter; Harefa, Idarni; Laia, Otanius (ProBisnis : Jurnal Manajemen, 2025)
Amidst increasing competition in the digital payment market, ZPay, operated by PT. ZPay Komunika Indonesia in Gunungsitoli, faces challenges in maintaining user preference. This study aims to analyze consumer behavior in choosing ZPay as a digital transaction service, focusing on factors influencing decision-making and the stages of the decision process. Using a qualitative case study approach, data were collected through observations, in-depth interviews, and documentation involving active ZPay users, the company owner, employees, and customers. Findings reveal that cultural, social, personal, and psychological factors significantly influence consumer choice. Key considerations include ease of use, transaction security, social influence, and positive prior experiences. The decision-making process comprises need recognition, information search, evaluation of alternatives, purchase decision, and post-purchase behavior. This research provides practical insights for ZPay in developing consumer-focused marketing strategies and contributes to academic literature on digital consumer behavior. The study emphasizes the importance of aligning services with consumer expectations to enhance satisfaction, loyalty, and competitiveness in the rapidly evolving digital economy.